DIFFERENCES IN VOLUNTARY COUNSELLING AND TESTING (VCT) COMPLIANCE RATES AS WELL AS FACTOR THAT INFLUENCE WPS AND WPSTL AT MADIUN REGENCY - Hanifah Ardiani; Avicena Sakufa Marsanti (Universitas Islam Negeri Alauddin Makassar, 2021)
The number of WPS and WPSTL visits in 2017 on VCT services in localization and karaoke places in Madiun Regency is still relatively low. According to the Ministry of Health, VCT services must be done 1 time in 3 months or 4 times a year (100%). In 2017 in Madiun Regency from the target of 100% risk group doing VCT, only reached 42.7% who did VCT in the WPS group and 72.7% in the WPSTL group. Cases of HIV / AIDS from year to year have increased significantly enough to require further treatment, especially in Madiun Regency. Of the 197 WPS and WPSTL in Madiun Regency, 89 (45.18%) were HIV/AIDS positive. One of the causes of the high incidence of HIV / AIDS cases in Madiun Regency is due to the low level of VCT service visits. This study used a cross sectional study design with a sample number of 49 WPS and 19 WPSTL based on the results of the calculation of the slovin sample formula. Sampling techniques using purposive sampling. The free variables in the study were peer knowledge, attitudes and support, while the bound variables were VCT compliance. Data analysis uses univariate, bivariate analysis using chi square and multivariate with logistic regression. External to this study is an article published in an accredited national journal.